Valorização Energética de Lodos de Sistema de Tratamento de Efluentes da Indústria de Abate e Processamento de Carnes Via Codigestão Anaeróbia - Fagnani, Katia Cristina (2023)
The main organic waste from the meat slaughtering and processing industry has been sludge produced during physical-chemical flotation process (flotation sludge - FL) and the surplus sludge from the activated sludge system (AS). FL is a waste product with a high lipid and protein content, and its treatment with anaerobic digestion has been reported in literature since it has caused problems on reactor stability, and increased acidity due to the accumulation of short-chain fatty acids (SCFA) and ammonia, factors that can cause reversible or total inhibition of methanogenic archaea. Problems related to the cost of disposal and volume of waste generated incited this study, with the opportunity to treat both wastes within the industry itself. Therefore, the main objective of this study was to evaluate the anaerobic co-digestion of floated sludge with activated sludge to treat effluents from poultry and tilapia meat slaughtering and processing industry, in the Western region of Paraná, in a 16-L continuous complete mixing reactor (CSTR The effect of increasing floated sludge concentration (30 to 100% v/v) was analyzed regarding methane generation and organic load removal for energy recovery. The reactor operation was divided into phases, defined according to the content of flocculated sludge in substrate, which consisted of Phase I: reactor start-up (inoculum+20%FL+80%AS) and treatments from 1 to 4 with concentrations ranging from 30 to 90% flocculated sludge; and Phase II: acclimatization period (70%FL+30%AS) and treatments with 70% FL; 90% FL and 100% FL. These phases differed in terms of OLR values: Phase I operated at 0.21 to 0.54 kg SV.m-3.d-1, and Phase II opera ed with undiluted waste at 1.53 to 2.53 kg SV.m-3.d-1. HRT was 20 days for all treatments. It can be concluded from Phase I that the content increase of floated sludge from 30 to 90% contributed to an increase in biogas and methane production, and these results contributed to the operation strategy for the next phase. In Phase II, operation occurred at 70, 90 and 100% FL. It can be concluded that the volumetric production of biogas (VPB) increased, but the treatments showed different stability and performance behaviors. The volumetric production of methane (VPM) among treatments with 70%, 90% and 100% FL were 513.67; 597.61 and 595.58 mLCH4.L-1.d-1, respectively, and showed no statistical differences. The methane yields for 70% FL and 90% FL treatments were 417.20 and 529.01 mLCH4 g-1 SVrem, respectively, and did not differ statistically. The taxonomic analysis showed a high relative abundance for methanogenic archaea. The 90% FL treatment remained stable during operation (AI/AP:0.31) and showed the highest relative abundance of methanogenic archaeae of the Methanosarcina genus (59.15%). There was a decrease in methane yield when the operation occurred at 100% FL. This showed an accumulation of SCFA (9.7 g.L-1) and free ammonia (FA) (301 mg.L-1), which testified the inhibition of methanogenic archaeae (25.99%). Regarding organic load removal, the Phase II treatments showed COD removal efficiencies of 39.96, 51.77 and 70.89%, COD of 52.34, 51.11 and 60.11%, VS of 80.51, 72.59 and 78.19% and OG of 65.41, 71.11 and 62.60%, respectively for the 70% FL, 90% FL and 100%LF treatments. Considering the VPB of the 90% FL treatment, a case study was carried out to simulate the potential for biogas generation. Thus, it was concluded that the respective industry, with daily slaughter of 600 thousand poultries and 100 thousand tilapia, could generate 11707 m3.d-1 of biogas and 7314 m3.d-1 of methane daily, which could be used as electricity, heat or biomethane. Lastly, it can be concluded that codigestion is a promising approach for energy recovery of flocculated sludge from the meat slaughtering and processing industry. It can also contribute to the sustainable management of industrial waste and the production of clean, renewable energy.